2019
DOI: 10.5194/hess-2019-108
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spatial and temporal variation in river corridor exchange across a 5th order mountain stream network

Abstract: Abstract. Although most field and modeling studies of river corridor exchange have been conducted a scales ranging from 10’s to 100’s of meters; results of these studies are used to predict their ecological and hydrological influences at the scale of river networks. Further complicating prediction, exchange are expected to vary with hydrologic forcing and the local geomorphic setting. While we desire predictive power, we lack a complete spatiotemporal relationship relating discharge to the variation in geologi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 76 publications
4
35
0
Order By: Relevance
“…This scale dependence may arise from variable dispersal kernels (e.g., along preferential 351 flow paths) or from vertical hydrological exchange at the stream reach scale, which could 352 generate idiosyncratic spatial variation in community structure. In our study system, it has been 353 shown that vertical hydrological exchange plays a more important role in headwaters than in 354 downstream reaches (Ward et al 2019), suggesting that vertical fluxes may be responsible for 355 disrupting the species sorting process predominantly in the headwater reaches. If so, stochastic 356 dispersal may increase in importance downstream as channels widen and the relative importance 357 of vertical exchange diminishes.…”
Section: Compositionally Distinct Planktonic and Sediment-associated mentioning
confidence: 86%
“…This scale dependence may arise from variable dispersal kernels (e.g., along preferential 351 flow paths) or from vertical hydrological exchange at the stream reach scale, which could 352 generate idiosyncratic spatial variation in community structure. In our study system, it has been 353 shown that vertical hydrological exchange plays a more important role in headwaters than in 354 downstream reaches (Ward et al 2019), suggesting that vertical fluxes may be responsible for 355 disrupting the species sorting process predominantly in the headwater reaches. If so, stochastic 356 dispersal may increase in importance downstream as channels widen and the relative importance 357 of vertical exchange diminishes.…”
Section: Compositionally Distinct Planktonic and Sediment-associated mentioning
confidence: 86%
“…We used the StorAge Selection (SAS) approach to interpret conservative solute transport through the study reach [94][95][96]. Briefly, the SAS approach considers outflow as a combination of waters sampled from different ages within the total storage volume between the injection and observation locations.…”
Section: Storage Selection Modelingmentioning
confidence: 99%
“…Moreover, common model formulations are not appropriate for interpreting experimental data in intermittent streams, as they require the presence of a continuously flowing stream [91][92][93], though exceptions do exist [23]. To overcome these limitations, new approaches, such as the StorAge Selection (SAS) model, take transport as a continuum and can simulate continuously variable discharge [94][95][96].…”
Section: Introductionmentioning
confidence: 99%
“…Further, data needed to validate scaling estimates are not available because monitoring networks are typically not designed for nested, network scale analyses within individual watersheds that can be used to further constrain scaling dynamics. River networks therefore remain an important "missing scale" in our observational toolkit of in situ measurements 45 . Superlinear scaling of cumulative biogeochemical processing results from efficient resource use due to disproportionate material inputs from the landscape in headwaters, upstream-downstream connectivity, and high uptake potential downstream, underscoring the role of river networks to functioning of the earth system.…”
Section: Merging Observations With Scaling Theorymentioning
confidence: 99%